Two Discrete RuCp* (Cp*=Pentamethylcyclopentadienyl) Binding Modes of N‐Confused Porphyrins: Peripheral π Complex and Sitting Atop Ruthenocenophane Complex by Skeletal Transformation. Issue 26 (16th April 2018) - Yamamoto, Takaaki; Mitsuno, Koki; Mori, Shigeki; Itoyama, Shuhei; Shiota, Yoshihito; Yoshizawa, Kazunari; Ishida, Masatoshi; Furuta, Hiroyuki
Abstract: Complexation of a RuCp* cation with N‐confused tetraarylporphyrins (NCPs) forms directly bound ruthenium(II) pentamethylcyclopentadienyl (Cp*) π‐complex on a specific meso ‐aryl group (e.g., phenyl) neighboring peripheral imino nitrogen of NCPs in high yields. In contrast, in the case of NCPs bearing bulky meso ‐substituents (e.g., 3, 5‐di‐tert‐butylphenyl), new ruthenocenophane‐like complex embedded on an N‐confused calix[4]phyrin was formed through multiple C−H bond activation of methyl groups of Cp* ligand. The mechanistic insight into the formation of the ruthenocenophane was derived from DFT calculations. Abstract : Playground for organometallic complex : N‐Confused porphyrins form two types of organometal complexes with a RuCP* cation. The η 5 ‐coordinated ruthenium cation is localized in the different places of NCP; a π‐coordination on the meso ‐aryl ring, and a sitting atop at the inner NNNC core, controlled by the bulkiness of the peripheral rings (see figure).